2017
DOI: 10.1097/mpa.0000000000000843
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic Patient-Derived Pancreatic Cancer Xenografts Engraft Into the Pancreatic Parenchyma, Metastasize, and Induce Muscle Wasting to Recapitulate the Human Disease

Abstract: Through the orthotopic implantation technique described, we demonstrate a highly reproducible model that recapitulates both local and systemic aspects of human PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 32 publications
(34 reference statements)
2
40
0
1
Order By: Relevance
“…When tumours reached 1.5 cm in diameter, they were resected, portioned into two‐by‐two millimetre sections, and implanted into mice orthotopically, sutured to the pancreas. The surgical procedure was performed using previously described methods . Although not tested here, others have shown a high degree of genetic stability in PDXs when compared with the original pancreatic cancer specimen, and we have previously demonstrated that PDXs retain morphological characteristics of the original pancreatic cancer specimen .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When tumours reached 1.5 cm in diameter, they were resected, portioned into two‐by‐two millimetre sections, and implanted into mice orthotopically, sutured to the pancreas. The surgical procedure was performed using previously described methods . Although not tested here, others have shown a high degree of genetic stability in PDXs when compared with the original pancreatic cancer specimen, and we have previously demonstrated that PDXs retain morphological characteristics of the original pancreatic cancer specimen .…”
Section: Methodsmentioning
confidence: 99%
“…This native environment is crucial in determining the biological behaviour of both the tumour and subsequent systemic response that induces cachexia . Tumour metastasis to the liver and lungs occurs in this model, which has been shown to be an important factor in the cachectic syndrome and is not a common feature in many pre‐clinical cancer cachexia models . Furthermore, by transplanting tumours from PDAC patients into mice, cachexia is investigated through the lens of soluble factors derived from a patient tumour, which likely varies between individual cancer patients .…”
Section: Introductionmentioning
confidence: 99%
“…This has the obvious advantage of allowing the study of organ-specific tumor microenvironment with increased accuracy and higher genetic heterogeneity and stability compared to the traditional xenograft models, similarly to GEM models. In particular, this was demonstrated for both orthotopic and subcutaneous engraftment of patient-derived pancreatic tumor (154,155). However, some data suggested that orthotopic engraftment of pancreatic tumor cells within mice's pancreas could induce systemic inflammation distinct from that observed in subcutaneous engraftments, leading toward more severe SM wasting [e.g., (154)].…”
Section: Discrepancies: From the Laboratory To The Clinical Practicementioning
confidence: 99%
“…This previous work has focused on the effects of nicotine in PDAC cells. Up to 80% of PDAC tumor volume is, however, composed of tumor-associated stroma (TAS) [15]. The vast array of signaling that occurs in the tumor microenvironment between TAS and cancer cells has been poorly characterized, and the role of nicotine in TAS is largely unstudied.…”
Section: Introductionmentioning
confidence: 99%